2015
DOI: 10.1371/journal.pone.0129994
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of Elastin Complex Receptor during In Vitro Aging Is Related to Modifications in Its Intrinsic Sialidase Activity and the Subsequent Lactosylceramide Production

Abstract: Degradation of elastin leads to the production of elastin-derived peptides (EDP), which exhibit several biological effects, such as cell proliferation or protease secretion. Binding of EDP on the elastin receptor complex (ERC) triggers lactosylceramide (LacCer) production and ERK1/2 activation following ERC Neu-1 subunit activation. The ability for ERC to transduce signals is lost during aging, but the mechanism involved is still unknown. In this study, we characterized an in vitro model of aging by subculturi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 60 publications
1
14
0
Order By: Relevance
“…Our experiments are the first to show that the VGVAPG peptide in a wide range of concentrations (100 pM to 100 µM) increased ROS production in astrocytes. To date, it has been described that EDPs induce ROS production in murine monocyte and human fibroblasts [ 17 , 18 , 27 ]. Gmiński et al [ 19 ] stated that κ-elastin increased both the activity of antioxidant enzymes (SOD, CAT, GSH-Px) and the lipid peroxide concentration within fibroblasts [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our experiments are the first to show that the VGVAPG peptide in a wide range of concentrations (100 pM to 100 µM) increased ROS production in astrocytes. To date, it has been described that EDPs induce ROS production in murine monocyte and human fibroblasts [ 17 , 18 , 27 ]. Gmiński et al [ 19 ] stated that κ-elastin increased both the activity of antioxidant enzymes (SOD, CAT, GSH-Px) and the lipid peroxide concentration within fibroblasts [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ROS increased mRNA expression of elastin in human skin fibroblasts in vitro [ 16 ]. Simultaneously, EDPs have been reported to induce ROS production in monocytes and human fibroblasts, thus accelerating the ROS generation process [ 17 , 18 ]. On the other hand, EDPs also increase the activities of antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT) or glutathione peroxidase (GSH-Px), with a simultaneous increase in lipid peroxidation in human fibroblasts [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, our group has demonstrated that ERC uncoupling observed during ageing involves a rise in basal Neu-1 activity to a level too high to be modulated by EDP stimulation. 42 Consequently, EDPmediated lactosylceramide production and Neu-1 sialidase activity are reduced in ageing cells. These results, proposing that age-related ERC uncoupling could originate from its inability to regulate Neu-1 activity and lactosylceramide production, are of crucial importance considering the fact that EDP biological effects could not only vary during ageing, but also that pharmacological approaches targeting this peculiar receptor have to be adapted.…”
Section: The Elastin Receptor Complexmentioning
confidence: 99%
“…EBP possesses two functional binding sites: the elastin site on which EDP binding triggers signaling pathways, and the galactolectin site whom occupancy by galactosugars induces EDP release and dissociation of the complex ( Mecham et al, 1991 ). When EDP bind to EBP, neuraminidase-1 is activated and catalyzes the desialylation of adjacent gangliosides such as GM 3 [ N -acetylneuraminic-α-(2-3)-galactosyl-β-(1-4)-glucosyl-(1-1′)-ceramide] generating lactosylceramide (LacCer) production ( Rusciani et al, 2010 ; Scandolera et al, 2015 ). LacCer is a second messenger able to activate intracellular signals.…”
Section: Receptors and Signalingmentioning
confidence: 99%